Examining the Arab Spring Phenomenon in Descriptive Analysis of Structuralism - Atief Arezal Fatah; Abrar Abrar (Yupa: Historical Studies Journal, 2025)
The discourse on the Arab Spring is a popular research theme among international geopolitical researchers, especially those who pay special attention to the ups and downs of the crisis in the Middle East & North Africa region. This article tries to examine and analyze the factors that led to the Arab Spring from a Structuralism perspective. There are 3 main discussions, namely: Arab Spring: Arab Revolt Movement, Tribalism, Sectarianism & Authoritarianism of the Arab World, United States GWOT & the Rise of Jihadist Militia after the Arab Spring.